Civic Councils for Education. Critical discourse analysis - Kosiorek, Małgorzata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The aim of this article is to describe the genesis and activities of the Civic Council for Education project and to present it as an activity leading to the development and possible changes in the socialisation of Polish educational policy. The undertaken analysis concerns the reconstruction of knowledge of the society about the professional situation of teachers and their attitude towards current educational reality. The considerations were presented using critical discourse analysis.